2021
DOI: 10.1149/1945-7111/abe3f1
|View full text |Cite
|
Sign up to set email alerts
|

High Porosity Single-Phase Silicon Negative Electrode Made with Phase-Inversion

Abstract: Herein we present a Si electrode fabrication process that includes a phase-inversion step subsequent to slurry-based electrode casting and discuss its consequences for Si//Ni0.6Co0.2Mn0.2O2 cell performance. The phase inversion consists of extracting 1-methyl-2-pyrrolidinone with water and the concomitant coagulation of the polyacrylonitrile binder. Phase inversion improves capacity retention by 50% during C/5 cycling of Si//Ni0.6Co0.2Mn0.2O2 coin cells between 3.0 and 4.2 V. Phase-inversion Si electrodes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…5b). Both electrodes started with initial total porosities of 50%-55%, 80,81 however the binder in the PAN electrodes has been carbonized via pyrolysis. Carbonization of PAN via heat treatment above 500 °C results in a several order of magnitude enhancement in electrical conductivity, but a concomitant ten-fold decrease in elongation due to the transformation from the aliphatic to cyclic polymer backbone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). Both electrodes started with initial total porosities of 50%-55%, 80,81 however the binder in the PAN electrodes has been carbonized via pyrolysis. Carbonization of PAN via heat treatment above 500 °C results in a several order of magnitude enhancement in electrical conductivity, but a concomitant ten-fold decrease in elongation due to the transformation from the aliphatic to cyclic polymer backbone.…”
Section: Discussionmentioning
confidence: 99%
“…We also fabricated silicon electrodes with pyrolyzed polyacrylonitrile (PAN) binder (Goonvean Fibres Ltd) in the same method as the air-dried electrodes described in another previous publication. 81 Briefly, electrode components were mixed in a planetary mixer with N-methyl-2-pyrrolidone to form a slurry, coated onto copper foil by doctor blade, dried at 75 °C overnight, followed by 2 h under vacuum, then heat treated in a tube furnace under high purity nitrogen (275 °C for 1 h then 700 °C for 1 h) before coin cell preparation. The formulation of these electrodes was 84.8/0.4/8.5/6.3 silicon (2 μm)/single-walled carbon nanotubes (SW-CNT, Tuball)/ carbon nano fiber (CNF, Pyrograf)/pyrolyzed polymer, referred to as the "PAN" electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been reported to utilize a variety of porous silicon materials fabricated with various methods as negative electrodes for LIBs. [27][28][29][30][31] For example, Yao et al synthesized silicon hollow nanoparticles using SiO 2 solid spheres as templates for silicon deposition, and the aggregate hollow nanospheres with a uniform pore size of ∼350 nm were formed after etching the templates. 32 They showed that the prepared electrodes exhibited high gravimetric capacity even after 700 cycles (∼1,400 mAh g −1 ).…”
mentioning
confidence: 99%